230 years of AGN monitoring: Frequency of cloud occultation events in AGN & constraints for clumpy torus models. Issue Volume 9:Issue S304(2013) (25th July 2014) - Krumpe, Mirko; Markowitz, A.; Nikutta, R.
Abstract: We systematically search for discrete absorption events in the vast archive of the Rossi X-ray Timing Explorer. This includes dozens of nearby type I and Compton-thin type II AGN and covers timescales from days to over a decade for individual objects. We are sensitive to discrete absorption events due to clouds of full-covering, neutral or mildly-ionized gas with columns 10 22−25 cm −2 transiting the line of sight. We detect 13 eclipse events in 8 objects, roughly tripling the number of previously published events from this archive. Despite sensitivity to events with N H up to 10 24−25 cm −2, we measured no Compton-thick eclipses in our sample. Peak column densities span 2.5–19 × 10 22 cm −2 . Event durations span hours to months. We infer the clouds distances from the black hole, assuming Keplerian motion, to span 0.2–80 × 10 4 Schwarzschild radii. We find no statistically significant difference between the individual cloud properties of type I and II objects. The presence of eclipses in both type Is and IIs argues against sharp-edged cloud distributions. The type II AGN show a level of "base-line" X-ray absorption that is consistent with being constant over timescales from 0.6 to 8.4 yr. This can either be explained by a homogeneous medium, or by X-ray-absorbing clouds that each have NH ≪ 10 22 cm −2 . Considering the "selection function" of the monitoring, we derive the probability of cloud occultation events. Finally, we derive the first X-ray statistical constraints for clumpy-torus models.